Reviving tourism industry post-COVID-19: A resilience-based framework. (January 2021) - Sharma, Gagan Deep; Thomas, Asha; Paul, Justin
Abstract: The COVID-19 pandemic struck the tourism industry severely. Based on the review of 35 papers that studied the tourism industry in the wake of the pandemic, we propose a resilience-based framework for reviving the global tourism industry post-COVID-19. Our framework outlines four prominent factors for building resilience in the industry: government response, technology innovation, local belongingness, and consumer and employee confidence. We argue that using such inclusive resilience; the tourism industry may transform into a new global economic order characterized by sustainable tourism, society's well-being, climate action, and the involvement of local communities. We also offer directions for future research in the area. Highlights: We propose a resilience-based framework for reviving the global tourism industry. The tourism industry may transform into a new global economic order. Sustainable tourism, well-being of society, and climate action mark the new order.